GENDER DIFFERENCES IN COVID-19 VACCINATION IN UKRAINE - Mamontova, T.V. (World of Medicine and Biology, 2023)
The COVID-19 pandemic is among the greatest challenges for the worldwide. Vaccine development is an effective weapon against pandemic development. But there is a paucity of data of COVID-19 vaccine data by sex/gender in Ukraine. The purpose of the study was to assess diversity in COVID-19 vaccination among gender groups of Ukrainian population. A retrospective-archive study was conducted in Ukraine from 24 February 2021 to 16 January 2022. The obtained data showed in trends gender differences in COVID-19 vaccination status. Women preferred vaccination with Pfizer/Biontech and AstraZeneca vaccines more often than men. Significantly higher level of weekly cases among persons who received two doses than one dose of Pfizer/BioNTech vaccine with as among males (p